Multifarious Subalternity of Underprivileged Women in Nepal - Khan, Najia (Patan Prospective Journal, 2023)
This paper explores the potentials of Nepalese women by unearthing obstacles and challenges they are facing because of prevailing inequality and discrimination in almost all sectors across Nepal. The article undertakes gender diversity and its problems and then analyzes them. Eventually it extends some suggestions on empowering females so that they can lead prestigious lives. Since Nepal is patterned in the blueprint of male supremacy, women’s condition is pathetic and bizarre. Pathetic narratives about gender inequality and discrimination pervade both urban and rural Nepal. Besides, religious social systems especially the Hindu social system that predominantly believes in vertical hierarchy in terms of caste, gender, and class, engrosses the women's rights by discarding their genuine demands. Nevertheless, subaltern theorists see hopes for the amendment in their conditions provided women are empowered economically, culturally and politically. Economic and political strengths of women can leverage their positions in society at large. To counter the males, the females must be made capacitated.